2023
DOI: 10.1002/cpp.2838
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic growth in colorectal cancer survivors: A systematic review

Abstract: Objective The diagnosis of cancer is an adverse event; nevertheless, it can also exert positive changes on survivors, such as posttraumatic growth (PTG). This review aims to integrate researches on PTG in colorectal cancer (CRC) survivors, including manifestations and prevalence of PTG, factors associated with PTG and interventions on PTG. Methods A systematic search was implemented on six databases to identify studies on PTG in CRC survivors published in English or Chinese from October 1995 to May 2022. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 76 publications
(262 reference statements)
0
24
0
Order By: Relevance
“…The couple‐based PTG programme for CRC patient–spousal caregiver dyads is an intervention proposed to enhance CRC couples' PTG levels and facilitate better health‐related outcomes. The intervention plan was formulated based on the results of the previous studies (Wang et al, 2023) and PTG affective‐cognitive processing model (Joseph et al, 2012). Detailed information has been shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The couple‐based PTG programme for CRC patient–spousal caregiver dyads is an intervention proposed to enhance CRC couples' PTG levels and facilitate better health‐related outcomes. The intervention plan was formulated based on the results of the previous studies (Wang et al, 2023) and PTG affective‐cognitive processing model (Joseph et al, 2012). Detailed information has been shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…The appraisal mechanisms have effects on the thought of a person and thus integrate it into his life narratives, which would, in turn, stimulate individual's psychological well-being (e.g., PTG). The whole process forms a feedback mechanism, implying that alterations in the changeable phases (event cognitions, emotional states, coping, social and environmental context and appraisal mechanisms) from a professional perspective could facilitate positive outcomes (e.g., PTG) for couples coping with CRC (Joseph et al, 2012;Wang et al, 2023). Thus, we have developed an intervention programme for the couples coping with CRC based on the PTG affective-cognitive processing model.…”
Section: Introductionmentioning
confidence: 99%
“…7 CRC negatively affects both patients and SCs, which lead to decreased QOL and adaptation abilities in the dyads. [8][9][10][11] Studies also indicated that PTG occurs in CRC couples during the cancer trajectory, 12,13 which benefits them in adapting and coping with the disease. Therefore, it is necessary to promote CRC couples to discover positive changes in the course of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to promote CRC couples to discover positive changes in the course of the disease. 13 To better understating the current research state of CRCrelated PTG, Wang et al, 13 conducted a systematic review on the topic. The review integrated CRC-related PTG manifestations, factors, and the interventions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation